2019
DOI: 10.1093/ofid/ofz296
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Transcriptional Changes in Circulating Monocytes of Acute Q Fever Patients

Abstract: Objective Although most patients recover from acute Q fever, around 20% develop Q fever fatigue syndrome (QFS), a debilitating fatigue syndrome that lasts at least 6 months. This study investigated transcriptional profiles of circulating monocytes and circulating cytokines as a subsequent mirror of myeloid cell function, 1 and 6 months after an acute Q fever infection. Methods Total RNA of circulating monocytes was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…2017 ). Yet, a recent study showed that RP11-13A1.1 was significantly downregulated in monocytes isolated from patients with Q fever, an infection caused by the zoonotic bacterium Coxiella burnetii ( Raijmakers et al. 2019 ), suggesting that this lncRNA may affect the immune response against nonfungal infections as well.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ). Yet, a recent study showed that RP11-13A1.1 was significantly downregulated in monocytes isolated from patients with Q fever, an infection caused by the zoonotic bacterium Coxiella burnetii ( Raijmakers et al. 2019 ), suggesting that this lncRNA may affect the immune response against nonfungal infections as well.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated increased concentrations of anti-inflammatory cytokines IL-10 and IL-1Ra at six months after acute Q fever infection. It was suggested that this was the result of altered transcriptional programming of myeloid cells [15]. As a result of this inflammatory dysregulation, Q fever patients might be more susceptible to infections, e.g., with SARS-CoV-2, and may have an increased risk of symptomatic disease and hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exposure to vaccines such as Bacille Calmette-Guerin (BCG) and small pox can induce long-lasting, heterologous immune effects mediated by epigenetic modifications in innate immune cells (trained immunity) ( Benn et al, 2013 ; Blok et al, 2015 ; Arts et al, 2016 ; Netea et al, 2020 ). Acute viral or bacterial infections also seem to induce global changes in immune responses over a considerable period of time ( Silveira et al, 2017 ; Raijmakers et al, 2019 ). Rhesus macaques experimentally infected with Zika virus have been shown to maintain altered frequencies of circulating monocyte and myeloid dendritic cell subsets up to seventy days post-infection ( Silveira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhesus macaques experimentally infected with Zika virus have been shown to maintain altered frequencies of circulating monocyte and myeloid dendritic cell subsets up to seventy days post-infection ( Silveira et al, 2017 ). During a six month follow-up, patients with acute Q fever have demonstrated long-lasting transcriptional changes in circulating monocytes and certain cytokines ( Raijmakers et al, 2019 ). In fact, various factors such as transportation, relocation, acclimation, social conditions and aging also can adversely impact the immune profile of macaques ( Didier et al, 2012 ; Capitanio & Cole, 2015 ; Nehete et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%